2022
DOI: 10.3389/fcell.2022.937753
|View full text |Cite
|
Sign up to set email alerts
|

Miro proteins and their role in mitochondrial transfer in cancer and beyond

Abstract: Mitochondria are organelles essential for tumor cell proliferation and metastasis. Although their main cellular function, generation of energy in the form of ATP is dispensable for cancer cells, their capability to drive their adaptation to stress originating from tumor microenvironment makes them a plausible therapeutic target. Recent research has revealed that cancer cells with damaged oxidative phosphorylation import healthy (functional) mitochondria from surrounding stromal cells to drive pyrimidine synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 248 publications
0
3
0
Order By: Relevance
“…Several studies have shown that the transferred mitochondria can exert their effect within a minimum of 45 cell passages (135 days) in vitro [ 53 ], while other studies discovered maintenance of acquired phenotype for at least 21 days [ 54 ]. The three common inducers of TNT formation typically work together: chemical or physical stressors, inflammatory conditions, and metabolic stress [ 55 ]. TNT formation can be promoted by hypoxia in various cancers, including ovarian and colon cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the transferred mitochondria can exert their effect within a minimum of 45 cell passages (135 days) in vitro [ 53 ], while other studies discovered maintenance of acquired phenotype for at least 21 days [ 54 ]. The three common inducers of TNT formation typically work together: chemical or physical stressors, inflammatory conditions, and metabolic stress [ 55 ]. TNT formation can be promoted by hypoxia in various cancers, including ovarian and colon cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the effect of transferred mitochondria can be exerted within at least 45 cell passages (135 days) in vitro 53 , while others demonstrate maintenance of acquired phenotype for at least 21 days 54 . The three common causes of TNTs formation typically work together: chemical or physical stressors, in ammatory conditions, and metabolic stress 55 . The hypoxia present in various cancers can promote the formation of TNTs, such as ovarian or colon cancer 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the droplet-based microfluidic system in enhancing the transplantation of mitochondria was also reported [22]. In the molecular aspect, proteins such as Miro 1 and Miro 2 proteins were found to be involved in mitochondrial trafficking [23]. Therefore, the natural or artificial transfer of mitochondria were broadly discovered.…”
Section: Introductionmentioning
confidence: 99%